The anointed church : toward a third article ecclesiology - Liston, Gregory J. (Minneapolis, Fortress Press, 2015)
The phrase Third Article Theology is used in two senses: first, to characterize a methodological approach that intentionally starts with the Spirit, and second, as the theological understanding that emerges from this approach. Over recent decades, Spirit Christology has utilized the approach of Third Article Theology to gain significant insight into the person and life of Christ. The Anointed Church extends this work, providing the first constructive and systematic ecclesiology developed through the approach of Third Article Theology. Gregory J. Liston argues that a pneumatological lens irreducibly informs the connection between other theological doctrines and ecclesiology. Utilizing this insight, the Church is examined from the vantage points of Christology and the Trinity through such a pneumatological lens. The constituent features of a Third Article Ecclesiology developed in this manner are compared and contrasted with critical evaluations of ecclesiological understandings developed through alternative approaches, particularly those of Barth, Zizioulas, and Volf.
Part I. Toward a third article ecclesiology. Third article theology -- A "Chalcedonian" spirit Christology -- Constructing a third article ecclesiology -- Part II. The church as sequel to the incarnation. Two contrasting Christological ecclesiologies -- The pneumatological union between Christ and the church -- A Christological third article ecclesiology -- Part III. The church as participant in trinitarian life. From the economic to the immanent Trinity -- From the immanent Trinity to ecclesiology -- Ecclesial communion in the Trinity -- A trinitarian third article ecclesiology.
Originally presented as the author's thesis (doctoral)--AUT University, 2013.
Includes bibliographical references (pages 365-391) and index.
Keywords: Jesus Christ -- Mystical body; Spirit christology; Trinity; Church; Holy Spirit